2014
DOI: 10.1159/000365309
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer in Inflammatory Bowel Disease: Epidemiology, Pathogenesis and Surveillance

Abstract: Background: Inflammatory bowel disease (IBD; including ulcerative colitis and Crohn's disease) is associated with an increased risk for colorectal cancer (CRC). Chronic mucosal inflammation is a key factor in the onset of carcinogenesis in IBD patients. Although most gene alterations that cause sporadic CRCs also occur in patients with IBD-associated CRC, some gene sequences and mutation frequencies differ between sporadic CRCs and IBD-associated CRCs. Summary: This review explores the incidence of CRC in IBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…IBD is associated with an increased risk of CRC in which the carcinogenesis of CAC depends on unique environmental, genetic, and immunologic factors compared with sporadic CRC [ 41 ]. Although genomic sequencing for patients with IBD using NGS technology has not been thoroughly investigated, recent studies regarding CAC have suggested that there are several mutational differences between patients with sporadic CRC and those with CAC.…”
Section: Discussionmentioning
confidence: 99%
“…IBD is associated with an increased risk of CRC in which the carcinogenesis of CAC depends on unique environmental, genetic, and immunologic factors compared with sporadic CRC [ 41 ]. Although genomic sequencing for patients with IBD using NGS technology has not been thoroughly investigated, recent studies regarding CAC have suggested that there are several mutational differences between patients with sporadic CRC and those with CAC.…”
Section: Discussionmentioning
confidence: 99%
“…In two recent meta-analyses, the overall incidence rate of CAC among 181,923 and 54,478 UC patients was 1.58 to 3 per 1000 patient years, respectively [ 20 , 21 ]. Although randomized trials to show the effectiveness of surveillance programs in reducing IBD-associated mortality are lacking, many retrospective case series studies have revealed a benefit for surveillance in patients with IBD [ 12 , 22 ]. For IBD patients entering a surveillance program, the standard of care includes periodic colonoscopic exams with protocol biopsies (4 quadrant biopsies every 10 cm) and targeted biopsies if a lesion is seen to detect dysplasia [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic mucosal inflammatory damage is one of the key factors linked with the inception of carcinogenesis in an IBD patient. Even though several genetic alterations that result in sporadic CRCs also take place in patients with IBD-associated CRC, certain gene sequences as well as mutation frequencies differ between IBD-associated CRCs and sporadic CRCs [50]. Several other risk factors ranging from genetics [51], environmental, lifestyle, and intrinsic gut factors [52] also contribute to CRC occurrence in individuals having IBDs.…”
Section: Risk Factors Of Ibd and Its Associated Crcmentioning
confidence: 99%